An Agrarian History of South Asia. - Ludden, David (New Cambridge history of India., 1999)
A comprehensive historical framework for understanding the regional diversity of agrarian South Asia from medieval times to the present day. As a comparative synthesis of the literature on agrarian regimes in South Asia, this book will be a valuable student resource.